Peran Teungku dalam Implementasi Pendidikan Karakter di Dayah (Suatu Kajian di Provinsi Aceh) - Ikhwani, Tgk; Yusuf, M. (peusangan, 2024)
One of the advantages of Dayah character education in Aceh Province is an education system that is developed consistently in forming moral and responsible Muslim individuals. The educational process at the Dayah (Islamic Boarding School) includes various sciences, especially religious knowledge which must be understood by the Aneuk Dayah (santri). Essentially, apart from making students knowledgeable with their education so that students are intelligent and have worldly insight, they must also be able to create noble values ​​or character, based on the Koran and al-Hadīth. By returning Ilāhiyyah values ​​to humans, so that they become humans with noble morals (insān kāmil), under the guidance of teachers (Teungku and/or Ustaz). Teungku's role in implementing character education in Dayah includes ta'ẓīm to teachers (Teungku), parents, ulama, good role models, good manners, simplicity, honesty, trustworthiness, responsibility and independence. The methods of character education in Dayah are those played by Teungku through uswah al-hasanah, 'adah al-hasanahal, giving gifts and 'iqab, the ibrah method, the mauī'ẓah method, the discipline method, the targhīb wa tahzīb method and the self-reliance method